Gender and Family Empowerment of Indonesian Migrant Workers through the BK-TKI Program in the Coastal Region of the Mandalika Special Economic Zone, Indonesia - Rahmawati, Ratih; Ramdani, Taufiq; Juniarsih, Nuning (Universitas Islam Sultan Agung, 2024)
Indonesian Migrant Workers (PMI) are the country's foreign exchange heroes who generate remittances, by rotating funds (wages) from the results of work abroad. Coastal areas have their own characteristics because they have distinctive potential as marine tourism that holds the potential for the development of productive businesses in coastal areas. This potential needs to be balanced with the ability to manage the potential of marine resources. However, the problems experienced by them such as inequality of remittance management practices and social problems. This study aims to determine the implementation of the development of migrant workers and their families in coastal areas from the bottom through theBuilding Indonesian Workforce Families program or BK-TKI program, this is a strengthening of migrant workers families so that they can reduce difficulties in managing remittances, avoid vulnerable conditions because migrant workers' families are left behind to work, and the possibility of migrant workers returning to work abroad for the next period so that migrant workers and their families are declared out of the poverty chain after implementing the program. This research is qualitative research with a case study approach and analyzed with Robert K. Merton's structural functionalism theory. Data on the conditions of implementation of the BK-TKI program in coastal communities were obtained for 3 months. The results show that the implementation of the BK-TKI program in this region only has 2 pillars running, namely the pillar of economic empowerment and guaranteeing the rights of migrant workers' children.